Cooperative and non-cooperative R&D in product innovation and firm performance - Karbowski, Adam (Journal of Business Economics and Management, 2019)
The aim of this article is to investigate the impacts of cooperative and non-cooperative R&D strategies on product innovation and firm performance. Based on the industrial economics literature and the optimisation model, R&D competition, R&D cartelisation, and full industry cartelisation strategies of firms operating on a market with differentiated goods and simultaneous price and quality competition are considered. It is showed that R&D cartelisation entails a loss of firm’s product innovation compared with R&D competition. However, profit-maximising firms do not prefer the R&D competition strategy. They prefer to pursue either R&D cartelisation or full industry cartelisation strategies, depending on the elasticity of demand with respect to the firm’s investment in R&D. The social cost of R&D cartelisation is a loss of product innovation, and the social cost of full industry cartelisation is both the loss of product innovation and the loss of consumer surplus due to a relatively high price and low output of the final product. The latter results carry significant implications for the modern business and public policy.